A quasi-experimental investigation of college students' ratings of two physical activity mobile apps with varied behavior change technique quantity. (November 2019) - Davis, Ashlee; Ellis, Rebecca
Background: An assessment of how users rate physical activity apps of varying behavior change technique content is necessary to understand if users recognize differences in an app's ability to promote physical activity. Objective: The purpose of this study was to compare user ratings of an app with a lower behavior change technique count to an app with a higher behavior change technique count. Method: Participants were randomly assigned to interact with either the high behavior change technique app or the low behavior change technique app using an iPad. Participants then completed a Mobile App Rating questionnaire. Results: The final sample included 83 participants with an average age of 22.66 years (SD = 2.13; range = 20–29). Independent t -tests revealed significant group differences for perceived impact, t (81) = 5.27, p < .001, g = 1.15, 95% confidence interval (0.69, 1.62); engagement, t (81) = 6.71, p < .001, g = 1.15, 95% confidence interval (1.02, 1.87); aesthetics, t (81) = 4.29, p < .001, g = 1.15, 95% confidence interval (0.50, 1.38); and subjective quality, t (81) = 6.46, p < .001, g = 1.15, 95% confidence interval (0.75, 1.42), with participants from the high behavior change technique group scoring these qualities more positively than participants from the low behavior change technique group. Conclusion: App users rated a physical activity app with higher behavior change technique content more favorably on aesthetics, engagement, subjective quality, and perceived impact than those with reduced behavior change technique content. Additional research is needed to understand how these perceptions influence users during the app selection process, as well as the efficacy of apps for promoting physical activity behavior change.